Leitura literária: uma prática como recurso para alfaletrar - SILVA, Gilmara Raiza Mota da (2023)
In recent centuries we have experienced a society that has practices and instruments that are in creasingly mandatory in writing and reading for subjects to be inserted into it. Literature, thro ugh literary reading is a mechanism that enables the teaching of children in the process of liter acy. The choice for the theme is justified by participating in the BLALLET study group (Toy Library and Literacy and Literacy Laboratory), the project develops monitoring from readings and studies on the theme literacy and literacy. The theme is of social relevance, because there is no debate in the Pedagogy course on Literature, as a methodology to contribute to the child 's learning in literacy. The aim of the study is to reflect on the importance of children's literatu re, from literary reading in the teaching of children in the process of literacy, thus contributing to the teaching process. The methodology consisted of bibliographic research, based on a qua litative approach, thus, GIL (2010, p.50) and MINAYO (2001, p. 14) were used. Among authors and authors who discuss the subject, we used CADEMARTORI (2010), COELHO (2000), LAJOLO (1993), ZILBERMAN (1995). In the first chapter, it brings the path of Literature. The next chapter covers literacy and literacy. The third chapter, brings what it says about literature in the RCN. Therefore, children’s literature contributes to the process of literacy and school literacy of children, because the literature promotes knowledge, possibilities, skills and languages according to their levels of understanding to the child.